THE DISCUSSION TECHNIQUE IN TEACHING SPEAKING BASED ON SCHOOL LEVEL CURRICULUM IN SECOND YEAR OF SMPN 3 KARTASURA - S U H A R T I N I , S U H A R T I N I (2007)
This research aims to describe the implementation of the Discussion Technique in Teaching Speaking Based on School Level-based Curriculum in the Second Year of SMPN 3 Kartasura. The research was done in SMPN 3 Kartasura from May, 21- Juni, 2007. The subject is the subject of the second class 8 (8F). There are 40 students. Type of research is action research. The action includes planning, implementing, observing, and reflection. In collecting data, the writer focuses on the discussion technique, the teaching-learning process, the student's activities, the teacher's activities or roles, the teacher and student's problem and problem-solving used by the teacher. Those are the components that the writer wants to analyze. The result of discussion technique in teaching speaking based school level based-curriculum in second year of SMPN 3 Kartasura follows: First, the teacher's problems are the limited capability of students and the mentality. Second, the student's problems are performance or readiness to study, shyness or nervousness, vocabulary, pronunciation, the independences of the students to learn and grammar. Third, the teacher problem solving are the teacher gives motivation and creates good relationship between the teacher and students, asks the students to present their discussion result well in their team or independently, gives example how to practice the presentation to submit their discussion result, and the teacher always corrects the mistakes of pronunciation, and grammar of students in their presentation in the last meeting. The conclusion of this research, it is not suitable for Junior High School if it used in teaching-learning process. The discussion technique is appropriate, if it used sometimes to loss the students bored in teaching learning process.